The Influence of Digital Influencer and Product Innovation on MSME Performance in Banda Aceh City by Brand Endorsement as a Mediator - Novrian, Robi; Mukhlis; Kesuma, T. Meldi (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to examine how Digital Influencers and Product Innovation affect the performance of Micro, Small, and Medium Enterprises (MSMEs) in Banda Aceh City, with Brand Endorsement playing a mediating role. The total population of MSMEs in Banda Aceh is 17,308. The study used primary data. Structural Equation Modelling (SEM) was used to analyze the direct effects, while the indirect effects were tested using the Sobel calculator. The results indicate that Digital Influencers and Product Innovation influence Brand Endorsement. Additionally, Digital Influencers, Product Innovation, and Brand Endorsement all influence MSME Performance. The study also found that Brand Endorsement acts as a mediator between Digital Influencers and Product Innovation in influencing MSME performance. This shows that the MSME Performance improvement model in Banda Aceh depends on the suitability of Digital Influencers, increased Product Innovation, and effective Brand Endorsement.